MVC techniques to normalize trunk muscle EMG in healthy women - Vera-Garcia, Francisco J.; Moreside, Janice M.; McGill, Stuart M. (Journal of electromyography and kinesiology, 2010)
Normalization of the surface electromyogram (EMG) addresses some of the inherent inter-subject and inter-muscular variability of this signal to enable comparison between muscles and people. The aim of this study was to evaluate the effectiveness of several maximal voluntary isometric contraction (MVC) strategies, and identify maximum electromyographic reference values used for normalizing trunk muscle activity. Eight healthy women performed 11 MVC techniques, including trials in which thorax motion was resisted, trials in which pelvis motion was resisted, shoulder rotation and adduction, and un-resisted MVC maneuvers (maximal abdominal hollowing and maximal abdominal bracing). EMG signals were bilaterally collected from upper and lower rectus abdominis, lateral and medial aspects of external oblique, internal oblique, latissimus dorsi, and erector spinae at T9 and L5. A 0.5 s moving average window was used to calculate the maximum EMG amplitude of each muscle for each MVC technique. A great inter-subject variability between participants was observed as to which MVC strategy elicited the greatest muscular activity, especially for the oblique abdominals and latissimus dorsi. Since no single test was superior for obtaining maximum electrical activity, it appears that several upper and lower trunk MVC techniques should be performed for EMG normalization in healthy women.